Betrayal intention in exporter-importer working relationships: Drivers, outcomes, and moderating effects - Leonidou, Leonidas C.; Aykol, Bilge; Fotiadis, Thomas A.; Christodoulides, Paul (My University, 2018)
Betrayal is a very common, but relatively under-researched, dark side phenomenon in inter-firm relationships that warrants investigation. We propose a conceptual model of the factors reducing betrayal intention in exporter-importer (E-I) working relationships and its resulting effect on actual betrayal. Using a random sample of 262 indigenous exporters of manufactured goods based in Greece, we confirm that betrayal intention in their relationships with foreign buyers is significantly and negatively affected by four key parameters, namely, trust, communication, long-term orientation, and social bonds. An importer’s betrayal intention is subsequently very likely to develop into actual betrayal in the relationship. However, this likelihood is lower in the case of older relationships, as well as those characterized by contractual obligation between the interacting parties.
Keywords: Betrayal; Buyer-seller relationships; Exporting/importing